Influence of a sputtered compact TiO2 layer on the properties of TiO2 nanotube photoanodes for solid-state DSSCs. (15th April 2017) - Krumpmann, A.; Dervaux, J.; Derue, L.; Douhéret, O.; Lazzaroni, R.; Snyders, R.; Decroly, A.
Abstract: TiO2 nanotube arrays (TNA) elaborated on transparent and conducting substrates are promising materials for photoanodes in dye-sensitized solar cells as the reduced dimensionality enhances their transport properties. TNA were obtained by anodization of Ti films deposited by magnetron sputtering on transparent conducting oxide-coated glass. This study presents the impact of introducing a compact TiO2 underlayer on the morphological, optical and electrochemical properties of the TNA photoanodes. The TNA morphology was found to be more regular with a TiO2 underlayer and the macroscopic homogeneity of the samples was also increased. This is ascribed to a strong reduction, in the presence of the compact TiO2 underlayer, of a side reaction leading to oxygen evolution and destructuring the TNA film during anodization. As a consequence, the optical and transport properties (characterized by UV–vis and electrochemical impedance spectroscopy, respectively) were improved, together with an increased photovoltaic efficiency. Graphical Abstract: Highlights: A sputtered TiO2 underlayer limits the side reaction of water oxidation during anodization, suppressing delamination issues of TiO2 nanotubes layers. The complete oxidation of titanium leads to an increased average transmittance in the visible from 65% to 74%. The electrical conductivity of the photoelectrodes with the underlayer is increased by an order of magnitude. The compact underlayer leads to an improved efficiency of these solid-state dye-sensitized solar cells, from 1.0% to 1.6%.